2020
DOI: 10.1097/ccm.0000000000004322
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Septic Shock in Patients With Malignancies: A Groupe de Recherche Respiratoire en Réanimation Onco-Hématologique Study*

Abstract: Objectives: Cancer affects up to 20% of critically ill patients, and sepsis is one of the leading reasons for ICU admission in this setting. Early signals suggested that survival might be increasing in this population. However, confirmation studies have been lacking. The goal of this study was to assess trends in survival rates over time in cancer patients admitted to the ICU for sepsis or septic shock over the last 2 decades. Data Source: Seven Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 60 publications
5
60
4
1
Order By: Relevance
“…There is no doubt that age and metastatic cancer as basic demographic information could be included in the model which plays unfavorable effects for the mortality. Whereas, survival in critically ill cancer patients with sepsis improved significantly over time but reasons or mechanisms for this condition haven't been identified [45]. In consideration of the source of infection, we found blood infection ranks the highest (38.49%), followed by MRSA screen (35.49%) and urine (17.36%), which indicates that we can perform empirical antibiotics treatment, but de-escalation or determination of whether or not to stop antibiotics or successful implementation of antimicrobial stewardship may help to improve a patient's clinical prognosis while preventing adverse outcomes [46].…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that age and metastatic cancer as basic demographic information could be included in the model which plays unfavorable effects for the mortality. Whereas, survival in critically ill cancer patients with sepsis improved significantly over time but reasons or mechanisms for this condition haven't been identified [45]. In consideration of the source of infection, we found blood infection ranks the highest (38.49%), followed by MRSA screen (35.49%) and urine (17.36%), which indicates that we can perform empirical antibiotics treatment, but de-escalation or determination of whether or not to stop antibiotics or successful implementation of antimicrobial stewardship may help to improve a patient's clinical prognosis while preventing adverse outcomes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to other reports, survival was higher for patients who underwent a first-line chemotherapy, had lobar ARDS and who received antibiotic treatment active on difficult-to-treat bacteria like Pseudomonas aeruginosa and Stenotrophomonas maltophilia [11]. The duration of neutropenia seems to be correlated with short-term mortality, while 30-day mortality is affected by organ dysfunction [12,13].…”
Section: Discussionmentioning
confidence: 76%
“…The decision to continue IV colistin has been taken considering the fact that the patient has been already exposed to levofloxacin, the possibility of a MDR germ and the unknown bioavailability of enterally administered TMP/SMX in a severely ill patient with reactive digestive ileus and gastric stasis (the IV form is not available in our country). Some retrospective studies have shown that, during ICU stay, the absence of neutropenia recovery and the presence of organ failure are associated with poor outcome in the critically ill patient with malignancy [11,12]. Furthermore, according to other reports, survival was higher for patients who underwent a first-line chemotherapy, had lobar ARDS and who received antibiotic treatment active on difficult-to-treat bacteria like Pseudomonas aeruginosa and Stenotrophomonas maltophilia [11].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A full code status with a time-limited trial and frequent reassessment should be applied in patients with a potentially reversible cause of deterioration or uncertain prognosis [76,77]. Neutropenia should no longer be considered a negative prognostic factor in managing these patients, even in allo−HSCT recipients [78][79][80]. A meta-analysis of more than 2000 HSCT patients in the ICU showed the main prognostic factors of mortality were multi-organ failures requiring support and uncontrolled graft versus host disease (GVHD), not septic shock, underlying malignancy or disease status, suggesting that they should not be used in the ICU transfer decision process [81].…”
Section: Management Of Critically Ill Neutropenic Patientsmentioning
confidence: 99%